Evaluation of perfusion by near-infrared fluorescence imaging in late pedicle obstruction of a parascapular flap to the lower extremity: a case report - Strübing, Felix; Bigdeli, Amir Khosrow; Schmidt, Volker-Jürgen; Kneser, Ulrich; Kotsougiani-Fischer, Dimitra (Microsurgery, 2018)
Abstract Late free flap failures due to pedicle obstruction are rare adverse events. The purpose of this report is to present a case in which the near-infrared indocyanine green video angiography (ICG-NIR-VA) was used to evaluate the perfusion in a compromised fasciocutaneous flap in the late postoperative period. A 55-year-old male patient, who initially suffered from an open tibial fracture, developed concurrent osteomyelitis with fistulae of the proximal tibia requiring excision. Reconstruction was achieved using a parascapular flap of 25???8?cm, anastomosed to an arterio?venous (AV) Loop in the adductor canal. On the 2nd postoperative day the patient developed a thrombosis of the AV-Loop. After thrombectomy, the postoperative course was uneventful. Seven weeks postoperatively the patient presented with a mottled, partially bluish and cold flap. Anticoagulation prophylaxis was stopped 2?days earlier. Angiography confirmed a thrombus in the arterial pedicle leading to flap ischemia. Near infrared guided fluorescence imaging revealed a delayed recapillarization of the proximal part of the flap closest to the vascular pedicle, albeit flap overall perfusion remained intact. Thus, no surgical intervention was undertaken. However, anticoagulation and prostaglandin therapy was initiated and the flap was salvaged. Genetic analysis uncovered a polymorphism in the prothrombin genes. The flap remained viable and without further complications until the last follow-up visit at 36?weeks after microsurgical reconstruction. The patient was fully mobilized with complete return to function. Near-infrared guided fluorescence imaging may be a viable tool for the assessment of late fasciocutaneous free flap complications and guide the decision-making process.
Gesehen am 23.04.2019